The shell collector : stories - Doerr, Anthony, 1973- (Scribner, 2011)
The exquisitely crafted stories in Anthony Doerr<U+2019>s debut collection take readers from the African Coast to the pine forests of Montana to the damp moors of Lapland, charting a vast physical and emotional landscape. Doerr explores the human condition in all its varieties<U+2014>metamorphosis, grief, fractured relationships, and slowly mending hearts<U+2014>conjuring nature in both its beautiful abundance and crushing power. Some of the characters in these stories contend with hardships; some discover unique gifts; all are united by their ultimate deference to the ravishing universe outside themselves.